An Assessment on Career Opportunities of Selected Bachelor of Scince in Office Administration at Bestlink College of the Philippines: Batch 2018 - 2019: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
According to the Commission on Higher Education, 517,000 new college graduates enter theworkforce each year. This statistic is taken from the Project Jobs Fit study conducted by theDepartment of Labor and Employment (DOLE) in 2009, which identified five industries asmajor sources of job openings or sources of employment: cyber services, hotels andrestaurants, construction, health and wellness, aviation, and other hospitality-relatedindustries. Among the most difficult-to-fill positions are those in these industries, whichinclude "to open positions for which a business has had trouble filling them because thereweren't any candidates, or because they didn't have the required training, knowledge, orcredentials, other factors, such as a preference for working abroad, a desire for a greaterwage, or a geographical issue.The research findings made it evident that a variety of factors, including projects, recitations,on-the-job training, and legal issues in the field, had an impact on alumni BSOA students'ability to locate employment opportunities. The survey results show that the majority of thealumni BSOA students had difficulties performing academically in terms of doing projectsand recipes.Researchers advise BSOA alumni students to participate in a variety of programs on Tesda.We also advised them to take advantage of any available opportunities, such as workexperience, in order to develop the knowledge and skills needed to secure employment inthe legal sector.
Keywords: Business Administration